1997
DOI: 10.1038/nm0997-1026
|View full text |Cite
|
Sign up to set email alerts
|

Thapsigargin-coated intraocular lenses inhibit human lens cell growth

Abstract: Cataract is responsible for rendering several million people blind throughout the world and is also by far the most common cause of low visual acuity. Although cataract surgery is common, routine and effective, posterior capsule opacification (PCO) occurs in 30-50% of patients following modern cataract surgery. This condition arises from stimulated cell growth within the capsular bag after surgery. The resulting decline in visual acuity requires expensive laser treatment, and PCO therefore prevents modern cata… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
81
0
1

Year Published

1999
1999
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(84 citation statements)
references
References 9 publications
1
81
0
1
Order By: Relevance
“…This drug delivery method has been used in the past for a number of molecules. 57,58 Interestingly, the effect of the MMP2 inhibitors GM6001, MMP2/9 inhibitor I, and MMP2/9 inhibitor II on ocular cell migration and viability were tested, along with longterm release rates from silicon-coated disks (a material commonly used to make IOLs). 59 Silicon disks coated with high concentrations of MMP2/9 inhibitor II reduced migration of FHL-124 cells by > 42%.…”
Section: Discussionmentioning
confidence: 99%
“…This drug delivery method has been used in the past for a number of molecules. 57,58 Interestingly, the effect of the MMP2 inhibitors GM6001, MMP2/9 inhibitor I, and MMP2/9 inhibitor II on ocular cell migration and viability were tested, along with longterm release rates from silicon-coated disks (a material commonly used to make IOLs). 59 Silicon disks coated with high concentrations of MMP2/9 inhibitor II reduced migration of FHL-124 cells by > 42%.…”
Section: Discussionmentioning
confidence: 99%
“…14,15 Coating polymethylmethacrylate lenses with thapsigargin effectively prevented LEC proliferation in an in vitro study of human capsular bags.…”
Section: Discussionmentioning
confidence: 99%
“…In cell culture, thapsigargin and 5-FU 25 mg/ml effectively killed the cells. The explanation for why thapsigargin is more effective in human LECs than in rabbit LECs is unknown; however, Duncan et al 14 proposed that the rabbit model often uses young animals whereas the human donor eyes most often are older. The rabbit cells are, therefore, more sensitive to stress than the human cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PCO severely compromises vision in many patients having cataract surgery, but there is as yet no completely effective method for preventing it (10). It has been shown that the use of an intraocular lens coated with thapsigargin, which kills LECs, prevents PCO ex vivo (11). Proliferation and directed migration of LECs are key events in PCO.…”
Section: Clinical Importancementioning
confidence: 99%